2015
DOI: 10.1364/prj.3.000a97
|View full text |Cite
|
Sign up to set email alerts
|

Passively Q-switched tri-wavelength Yb^3+:GdAl_3(BO_3)_4 solid-state laser with topological insulator Bi_2Te_3 as saturable absorber

Abstract: In this paper, we reported a multiwavelength passively Q-switched Yb 3 :GdAl 3 BO 3 4 solid-state laser with topological insulator Bi 2 Te 3 as a saturable absorber (SA) for the first time, to the best of our knowledge. Bi 2 Te 3 nanosheets were prepared by the facile solvothermal method. The influence of three Bi 2 Te 3 densities on the laser operation was compared. The maximum average output power was up to 57 mW with a pulse energy of 511.7 nJ. The shortest pulsewidth was measured to be 370 ns with 110 kHz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 38 publications
(44 reference statements)
3
14
0
Order By: Relevance
“…In 2013, Zhang et al demonstrated PQS SSLs using Bi 2 Se 3 as TI-based SA [19]. It arouses devotion of developing PQS SSLs employing TIs as SA in various wavelength and according TIs materials in recent years [19][20][21][22][23][24][25][26][27]. Regarding to the TI-based SAs, for example Bi 2 Te 3 , its low saturation intensity favours low threshold PQS and even QS-ML laser with moderate saturation fluence [24].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Zhang et al demonstrated PQS SSLs using Bi 2 Se 3 as TI-based SA [19]. It arouses devotion of developing PQS SSLs employing TIs as SA in various wavelength and according TIs materials in recent years [19][20][21][22][23][24][25][26][27]. Regarding to the TI-based SAs, for example Bi 2 Te 3 , its low saturation intensity favours low threshold PQS and even QS-ML laser with moderate saturation fluence [24].…”
Section: Introductionmentioning
confidence: 99%
“…As a comparison, the results of previous wok and this work is tabulated in Table I. Although repetition rate over 50 kHz were achieved (Gao et al 2018;Lee et al 2014;Li et al 2014;Lin et al 2018;Sun et al 2015;Yang et al 2018), these work require higher pumping power. This work also produces better results than our previous work (Salim et al 2017) that uses more complex process of implementing the SA.…”
Section: Resultsmentioning
confidence: 90%
“…Other works in this aspect used mechanical exfoliation method (Lee at al. 2014) and facile solvothermal method (Sun et al 2015). Recently, there have been research work that uses Bi 2 Te 3 thin flim to generate Q-switching pulses.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional SAs, such as Cr 4+ :YAG [6], GaAs [7], and semiconductor saturable absorber mirrors (SESAMs) [8], have gradually matured and been widely used in passively Q-switched lasers. But they have limitations in terms of a narrow absorption band and complicated preparation process [9]. By contrast, novel two-dimensional (2D) materials with the characteristics of a wide working band, fast recovery time, and convenient preparation have more advantages for obtaining Q-switched pulses.…”
Section: Introductionmentioning
confidence: 99%